CLIMATIC AND VEGETATION CHANGES IN THE BAIKAL REGION FOR THE LAST 5 MA: (ACCORDING TO PALYNOLOGICAL DATA ON THE BAIKAL SEDIMENTS) - Bezrukova E.V.; Kulagina N.V.; Letunova P.P.; Shestakova O.N. (My University, 1999)
A palynological analysis of the Baikal sediments from a 200 m deep borehole permitted tracing continuous climatic and vegetation changes in the Baikal region for the last 5 Ma (from the Early Pliocene). The sediment age was determined by paleomagnetic analysis, correlation of the obtained palynological data with the available material on this region and the adjacent areas, and extrapolation of sedimentation rate data. The complex of the obtained data evidences a relatively even sedimentation in the above period. The vegetation changes were caused mainly by the gradually progressing cooling of climate in the Tertiary and its strong fluctuations in the Quaternary. It has been established that there were at least three coolings, recurrent approximately every million years: 2.6-2.8, 1.6-1.8, and about 0.6 Ma BP. The change of landscapes proceeded regularly. First forest and forest-steppe small-leaved and conifer-broad-leaved landscapes gave way to forest dark-coniferous (spruce or cedar) ones, which, in turn, were replaced by forest light-coniferous (larch) and forest-tundra landscapes. When the cold periods ended, the regional vegetation again restored its initial, primarily forest, habit but, at the same time, became compositionally poorer because of the extinction of certain plant species.
Keywords: Pliocene; Quaternary; Cenozoic::Quaternary; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная; Кайнозой::Неоген::Плиоцен